Web gallery : Indonesia - Hendra Setiawan (2014)
Nowadays, due to mobile and instant lifestyle, people can easily travel from all around the world usually for business, entertainment, and tourism purposes. The growth of this kind of lifestyle has made South East Asia become one of the most popular tourism destination especially Indonesia. In order to equip foreigners while travelling to a new place, it is a need to have an application to provide information about local languages and items. The objective of this project is to create a database as well as user interface to show all information about local language (translation) and picture about local or traditional item. This project will go through several steps such as creating translation table, getting information from internet using a web crawler, applying TF-IDF term weighting for index searching, and building a web-based user interface to facilitate user in obtaining any information. All the parsing and calculation process are based on Java application and only the user interface is based on web-application.